Studi Konservasi Timpakul dan Moluska Berbasis Pengetahuan dan Sikap Masyarakat Desa Sungai Bakau, Kalimantan Selatan - Nurhikmah; Anang Kadarsah; Erma Agusliani (The Ethnobiological Society of Indonesia, 2021)
Knowledge and attitudes of the community toward conserving resources will guarantee the success of conservation programs. By knowing the knowledge and attitudes of the community, it will be easier to design an effective conservation and management strategies to maintain natural resources sustainably. This study aimed to document the knowledge and attitudes of the community regarding the conservation of timpakul and mollusks in the mangrove ecosystem of Sungai Bakau Village. The method used was questionnaire in the form of google form. The selection of respondents was based on the criteria of four professions, including farmers, fishermans, civil servants and students. There were 84 interviewed respondents. The data analysis used was Chi Square analysis using the SPSS. The results showed that the level of knowledge belonged to the sufficient category, while for the level of attitude most of the respondents had a positive attitude. There is a relationship between knowledge and attitudes towards respondents’ characteristics such as gender, profession, and study area in the efforts to conserve timpakul and mollusks in Sungai Bakau Village.